Literary Elite in Processes of Socio-Cultural Modernization of Russia in 1830-1850: Main Identificational Features and Peculiarities of Status and Role Identification - T. F. Arzhanykh (Научный диалог)
The process of formation of bases for self-identity are investigated as well as attribute characteristics of the humanitarian-artistic intelligentsia of Russia in 1830-1850. Specific features of the particular inter-class group of intellectuals of intelligentsia reflection are distinguished. The author identifies the self-identity of the noble intellectual elite outside the public service and a way of self-expression in literature as the key moments which determined the fate of pre-revolutionary Russian intelligentsia as a whole. A clear correlation between the development of public thought and literature, typical for the 19th century, is mentioned. Special attention is paid to understanding the innovative role of the literary elite in the processes of socio-cultural modernization. Objectives of the study determined the certain stratum of exploratory analysis: the study of linguistic structures and speech practices - discourses that existed among educated communities in 1830-1850. Socio-political and psychological factors that influenced the choice of axiological meanings and behaviour patterns of various reference groups of literary and historiosophical orientation are analysed. Socio-philosophical analysis of the spiritual experience of the Russian culture revealed the phenomenon of intellectual history - a contemplative-philosophical linguistic social code and variations of communicative-cognitive relationship to the world of Russian intellectuals. Russian dominant of social consciousness is explored as a social phenomenon and objective representative of the realities of culture. Connotative, additional meaning to the antithesis of “Russia - West” are examined in the context of raising the national question in philosophical variations and personal associations of the authors of psycho-mental models of world construction.